Pengaruh Tingkat Pengetahuan Gizi, Pola Konsumsi dan Tingkat Pendapatan Perkapita terhadap Kejadian Kekurangan Energi Kronik Ibu Hamil - Farhat, Yasir; Aprianti, Aprianti; Pratiwi, Niken (Jurnal Skala Kesehatan, 2025)
BackgroundIn 2018, the prevalence of chronic energy deficiency (CED) among pregnant women in South Kalimantan was 19.45%. In the working area of the Landasan Ulin Timur Health Center, Banjarbaru City, the prevalence reached 24.7%, the highest in the region. This study aims to analyze the influence of nutritional knowledge, consumption patterns, and per capita income on the incidence of CED among pregnant women in this area. MethodsThis research is observational-analytical with a case-control design. The population consisted of 361 pregnant women, and a sample of 44 participants (22 with CED and 22 without) was selected using purposive sampling. Data were gathered on nutritional knowledge, consumption patterns, per capita income, and CED incidence from secondary sources and analyzed using multiple logistic regression tests. ResultsMost pregnant women with CED had low nutritional knowledge (72.8%), poor consumption patterns (81.8%), and low income (90.9%). Nutritional knowledge significantly influenced CED incidence. ConclusionHealth workers should provide counseling to improve pregnant women's awareness and knowledge about CED prevention.